2005
DOI: 10.1093/nar/gki926
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic effects of abasic and oxidized abasic lesions in Saccharomyces cerevisiae

Abstract: 2-Deoxyribonolactone (L) and 2-deoxyribose (AP) are abasic sites that are produced by ionizing radiation, reactive oxygen species and a variety of DNA damaging agents. The biological processing of the AP site has been examined in the yeast Saccharomyces cerevisiae. However, nothing is known about how L is processed in this organism. We determined the bypass and mutagenic specificity of DNA containing an abasic site (AP and L) or the AP analog tetrahydrofuran (F) using an oligonucleotide transformation assay. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
47
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 50 publications
6
47
2
Order By: Relevance
“…It was suggested that MMR reduces the efficiency of recombination-mediated bypass when damage is present, and the studies presented here provide a concrete model for how the MMR system modulates pathway choice. Finally, our results may provide an explanation for the very low frequency (1-5%) of Pol -dependent lesion bypass observed in some plasmid-based yeast transformation studies (32,33), which contrasts with the high frequency (Ϸ60%) obtained when using lesion-containing singlestranded oligonucleotides (34,35). Based on the clear MMR dependence of TLS observed in the lys2⌬A746-NR system, we suggest that the specific use of MMR-defective host strains in the plasmid-based studies could account for the low TLS frequency.…”
Section: Discussionmentioning
confidence: 51%
“…It was suggested that MMR reduces the efficiency of recombination-mediated bypass when damage is present, and the studies presented here provide a concrete model for how the MMR system modulates pathway choice. Finally, our results may provide an explanation for the very low frequency (1-5%) of Pol -dependent lesion bypass observed in some plasmid-based yeast transformation studies (32,33), which contrasts with the high frequency (Ϸ60%) obtained when using lesion-containing singlestranded oligonucleotides (34,35). Based on the clear MMR dependence of TLS observed in the lys2⌬A746-NR system, we suggest that the specific use of MMR-defective host strains in the plasmid-based studies could account for the low TLS frequency.…”
Section: Discussionmentioning
confidence: 51%
“…Specifically, the use of ssOligos with differing sensitivities to MutS␣ and MutS␤ has revealed striking and unexpected strand differences in the activity of the two MMR complexes as well as unexpected differences in response to loss of MLH1. With a better understanding of the mechanism in place, this method should prove extremely valuable in studying the effects of defined base mismatches and damage on repair and replication in a chromosomal context (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Blocked DNA synthesis can be rescued either by a recombination/template switch mechanism or through the recruitment of specialized translesion synthesis (TLS) DNA polymerases (14). In yeast, TLS polymerase (Pol), together with the deoxycytidyl transferase Rev1, is required for most AP-site bypass, with a C nucleotide usually being inserted across from the template lesion (20,31,39). Depending on the base lost, AP-site bypass via TLS has the potential to be highly mutagenic.…”
mentioning
confidence: 99%